Understanding the National Union of Metalworkers of South Africa’s Evolving Policies on the Role of Renewable Energy in South Africa’s Mineral Energy Complex - Monaisa, Chere (University of the Witwatersrand, Johannesburg, 2024)
The concept of the just transition is widely regarded as organised labour’s response to the negative impact of climate change. It is used as a mechanism to reconcile the movement’s mandate to provide workers with decent jobs and the need to protect the environment. NUMSA is an example of a union that, during 2011-12, responded to the impact of climate change by developing its own policies and directly challenging government’s renewable energy policies. The union’s vision for South Africa is a socially owned renewable energy sector made up of a mix of energy parastatals, cooperatives, municipal-owned entities, and other forms of community energy enterprises. South Africa is heavily reliant on coal for its electricity generation. The government, the private sector, civil society, and organised labour mostly agree that there is a need to transition away from coal to renewable energy. Initially, the transition to renewable energy was framed as a choice between ‘jobs and environment’ and ‘jobs versus environment’. NUMSA’s vision of socially owned renewable energy displayed characteristics of active labour environmentalism that called for the transformative ‘jobs and environment with just transition’ despite its location in the fossil fuel sector. However, a series of events and decisions by a top leadership that is viewed as authoritarian and unenthusiastic about eco-socialism, has resulted in NUMSA adopting strategies in recent years that are, at best, seen as reactive and narrowly protecting workers – even though they purport to support a just transition to renewable energy. At worst, the union has been accused of anti-environmentalism and protecting coal and electricity workers regardless of the impact on the environment. It was this apparent shift and criticism of NUMSA that necessitated an analysis of its opposition to the closure of coal fired power stations to make way for renewable energy independent power producers. The findings point to a union that relies on its pioneering decarbonization policies to shield itself from legitimate criticism from labour climate activists and progressive environmental groups of its actual practice.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Arts (Labour, Policy, and Globalisation) to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; NUMSA; Just Transition; Climate Change; Renewable Energy; Organised labour; Trade unions; SDG-7: Affordable and clean energy